The Pseudotyped Replication-Deficient VSV with Spike from PEDV Induces Neutralizing Antibody Against PEDV - Jingxuan Yi; Huaye Luo; Kang Zhang; Lilei Lv; Siqi Li; Yifeng Jiang; Yanjun Zhou; Zuzhang Wei; Changlong Liu (Vaccines)
Background: Porcine epidemic diarrhea virus (PEDV) is a significant pathogen in swine, causing substantial economic losses worldwide. Despite the availability of existing vaccines, there is a critical need for novel vaccine platforms that ensure robust protection while maintaining safety. Methods: A recombinant replication-deficient vesicular stomatitis virus (VSV) vaccine, rVSV∆G-PEDV-S, was developed by pseudotyping the virus with the spike (S) protein from PEDV. To achieve high-titer pseudotyped rVSV particles, a stable Huh7 cell line expressing the PEDV S protein (Huh7-PEDV-S) was generated. The infectivity and replication capacity of rVSV∆G-PEDV-S were evaluated in PEDV-susceptible cell lines and Huh7-PEDV-S cells. The vaccine’s immunogenicity and safety were assessed in BALB/c mice vaccinated intramuscularly with rVSV∆G-PEDV-S. Results: The pseudotyped rVSV∆G-PEDV-S demonstrated infectivity in PEDV-susceptible cell lines and robust replication in Huh7-PEDV-S cells, while remaining replication-deficient in non-complementary cells. In vaccinated BALB/c mice, the vaccine elicited a strong humoral immune response, characterized by high levels of PEDV S1-specific IgG and neutralizing antibodies. No adverse effects, including weight loss or behavioral changes, were observed in the vaccinated mice, confirming the vaccine’s safety. Conclusions: The rVSV∆G-PEDV-S vaccine represents a promising platform for controlling PEDV outbreaks. Its replication-deficient design and pseudotyping methodology ensure safety and adaptability to emerging PEDV variants. These findings highlight the potential of rVSV∆G-PEDV-S as a safe and effective solution to the ongoing challenges posed by PEDV.